CORE STABILITY TRAINING EFFECTS ON LOWER LIMB REHABILITATION OF JUDOKAS - Cai,Haisheng (2022)
ABSTRACT Introduction Judo is a sport that presents a high incidence of sports injuries. Judo athletes want to master their skills to the maximum. Good physical conditioning is necessary to decrease the incidence of surgeries and achieve better results. Core stability exercises can discretely reduce the likelihood of lower limb injuries in judo athletes. Objective This paper examines the rehabilitation of core stability training effects on lower limb injuries in judokas by case studies. Methods A Chinese judo team member with a lower limb injury underwent core stability training. Isokinetic strength tests, body composition tests, and functional checks explored the athlete’s physical recovery after training. Results The athletes’ lower limbs progressed with good recovery (P<0.05). Additionally, a recovery in fitness level was also noted (P<0.05). Conclusion Core stability training positively affects recovery from lower limb injuries in judokas. Evidence level II; Therapeutic Studies - Investigating the results.